2020
DOI: 10.3390/ijerph17176028
|View full text |Cite
|
Sign up to set email alerts
|

The Homeostatic Theory of Obesity: An Empirical Verification of the Circle of Discontent with an Assessment of Its Relationship to Restrained and Uncontrolled Eating among Children and Adolescents

Abstract: The purpose of the present study was to provide an empirical verification of the Circle of Discontent with an assessment of its relationship to restrained and uncontrolled eating among children and adolescents. This study examined whether our results confirm a new hypothesized model. The total sample comprised 282 children and adolescents (148 girls and 134 boys; 141 participants with normal body weight and 141 with obesity). The mean age was 12.23 years (SD = 2.80), and the average BMI (body mass index) was 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…As shown by the research carried out so far, eating patterns and body image can play a very important role in developing obesity (e.g., (10,23,24), and one of the theoretical models explaining this is the Homeostatic Theory of Obesity (25). This model has also been empirically verified in studies conducted in a group of Polish children and adolescents (26). However, it is worth continuing research in this area to check how important social media in childhood are in shaping body image and eating patterns, especially given that (in general) children's and adolescents' use of social media has a significant impact on their body mass index (19).…”
Section: Introductionmentioning
confidence: 77%
“…As shown by the research carried out so far, eating patterns and body image can play a very important role in developing obesity (e.g., (10,23,24), and one of the theoretical models explaining this is the Homeostatic Theory of Obesity (25). This model has also been empirically verified in studies conducted in a group of Polish children and adolescents (26). However, it is worth continuing research in this area to check how important social media in childhood are in shaping body image and eating patterns, especially given that (in general) children's and adolescents' use of social media has a significant impact on their body mass index (19).…”
Section: Introductionmentioning
confidence: 77%
“…All subscales were used in this study. Reliability and validity were acceptable [44,45] and the Cronbach's alpha coefficient was: (a) food responsiveness: 0.86, (b) emotional under-eating: 0.68, (c) enjoyment of food: 0.84, (d) satiety responsiveness: 0.65, (e) desire to drink: 0.80, (f) slowness in eating: 0.79, (g) emotional over-eating: 0.82, (h) food fussiness: 0.82.…”
Section: The Child Eating Behaviour Questionnaire (Cebq)mentioning
confidence: 98%
“…Parents completed also the 35-item child eating behaviour questionnaire, which measures parents' assessment of children's eating-related behaviours [44,45]. It consists of eight subscales (food responsiveness, emotional over-eating, enjoyment of food, desire to drink, satiety responsiveness, slowness in eating, emotional under-eating, food fussiness, e.g., my child is difficult to please with meals, my child eats more when annoyed, if allowed to, my child would eat too much).…”
Section: The Child Eating Behaviour Questionnaire (Cebq)mentioning
confidence: 99%
“…One early application of the GTB was an effort to explain the causes of obesity (Annunziato and Grossman, 2016;DiClemente and Delahanty, 2016;Marks, 2015Marks, , 2016. Czepczor-Bernat et al (2020) provide an empirical verification of the theory with their study of restrained and uncontrolled eating among children and adolescents. Guided by the GTB, a study by Liu et al (2022) observed an inverted U-shaped relationship between BMI and happiness in China.…”
Section: The General Theory Of Behaviourmentioning
confidence: 99%